Visitor Perception of Kintamani Agro-ecotourism in Bali During The COVID-19 Pandemic - Surya Diarta, I Ketut; Artini, NI Wayan Putu (Media Konservasi, 2023)
The COVID-19 pandemic has hampered agro-ecotourism's economic, social, and environmental benefits. Previous studies have ignored visitor experiences, sustainability, and secondary data. A pandemic-era field assessment of Kintamani agro-ecotourism fills this gap. Purposive sampling was used to select 100 local visitors for the survey. Perceptual class intervals and WarpPLS 7.0 were used to analyze the data. Kintamani agro-ecotourism destination services and guest loyalty scored the highest. Attributes and service quality affected visitor satisfaction and loyalty, whereas the CHSE program measures did not. These findings include improving attributes and service quality, encouraging sustainability, collaborating with local communities and stakeholders, and developing innovative products and services for Kintamani agro ecotourism. Diverse market segments may be immersed in a region's culture and nature. Kintamani agro-ecotourism requires strong branding, marketing, and data-driven decision-making. Crisis management plans and sustainable infrastructure can help agro-ecotourism to survive unexpected disasters. Agro-ecotourism in Kintamani depends on the adaptation, innovation, and preservation of a region's natural and cultural legacy.